PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU YAYASAN PERGURUAN MARIA GORETTI PEMATANGSIANTAR - Nainggolan, Merry Christina; Lie, Darwin; Butarbutar, Marisi; Nainggolan, Lora Ekana (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2018)
The result of this study can be summarized as follows: 1. Theheadmaster’s leadership style, the work environment and the teacher’s performance’s good. 2. The results of regression analysis isŶ = 50,391 + 1,005X1 + 1,893X2, its means the headmaster’s leadership style and the work environment had a positive effect on teacher’s performance’s good. 3. The results of the analysis correlations get value r = 0,770, its means that there is a high and positive correlations between headmaster’s leadership style, work environment to the teacher’s performance’s. The level of teacher’s performance’s can be explained by headmaster’s leadership style and work environment as big as 59,3%. 4. The results of testing the hypothesis H0 is rejected, its means the headmaster’s leadership style and the work environment had a positve and significant effect to the teacher’s performance’s of simultaneous or partial. The suggestation of this research result are: 1. To realize an effective leadership style should the principal make a policy made with consultation with teachers 2. To realize a comfortable working environment needs to improve the physical work environment and non physical work environment 3. To optimize the performance of teachers, the agency should pay special attention to every teacher so that the teachers can complete the task well. Keywords: Headmaster’s Leadership Style, Work Environment and Theacher’s Performance